Physical–mechanical behavior of concretes exposed to high temperatures and different cooling systems. (16th February 2017) - Ercolani, Germán; Ortega, Néstor F.; Priano, Carla; Señas, Lilia
Abstract : Over their lifetime, concrete structures can suffer from different pathologies, one of them is exposure to high temperatures, which diminishes their load‐bearing capacity. This study describes how different concrete types were exposed to high temperatures. To simulate fire extinction, where the temperature of the overheated concrete descends suddenly, different cooling systems were applied: slowly cooling in the open air and fast cooling by spraying different water volumes. Several physical–mechanical characteristics were analyzed such as compressive strength, splitting tensile strength, porosity, capillary suction, and carbonation depth. Ultrasound nondestructive tests were conducted to quantify deterioration. A petrographic study using a stereomicroscope and microscopy of polarization was performed on thin sections to evaluate aggregate composition and concrete characteristics, focusing on interface areas. Physical and mechanical properties were affected by the increase in temperature, with damage worsening through the appearance of cracks and microcracks when water is used as a cooling system.